2011
DOI: 10.1002/smll.201100441
|View full text |Cite
|
Sign up to set email alerts
|

Probing a Bifunctional Luminomagnetic Nanophosphor for Biological Applications: a Photoluminescence and Time‐Resolved Spectroscopic Study

Abstract: A bifunctional luminomagnetic ≈30 nm Gd1‐xEuxVO4 nanophosphor is synthesized using a facile sol–gel method. The nanophosphor is observed to produce both paramagnetic behavior and a highly efficient red emission peaking at 618 nm. Probing the luminomagnetic nanophosphor using photoluminescence, time‐resolved spectroscopy, magnetization measurements, and a cytotoxicity assay reveal its suitability for biological applications, in particular, cell labeling and high‐contrast imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
73
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 27 publications
3
73
0
Order By: Relevance
“…Bifunctional nanomaterials that possess desirable properties in a single entity have been the focus of cutting edge science in recent years12345. For instance, nanomaterials with bifunctional properties such as luminescence, magnetism and high contrast bioimaging with magnetic resonance imaging (MRI) contrast capability can be used in a wide range of applications in biological systems such as bioimaging, diagnostic, and therapeutics234678.…”
mentioning
confidence: 99%
“…Bifunctional nanomaterials that possess desirable properties in a single entity have been the focus of cutting edge science in recent years12345. For instance, nanomaterials with bifunctional properties such as luminescence, magnetism and high contrast bioimaging with magnetic resonance imaging (MRI) contrast capability can be used in a wide range of applications in biological systems such as bioimaging, diagnostic, and therapeutics234678.…”
mentioning
confidence: 99%
“…12 In these studies, to ensure that any adverse reaction to the UCP would be observed, a maximum concentration of 1,000 μg/ml was used. Even at the very high concentration of 1,000 μg/ml, no cell death occured (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…It was measured at room temperature by a time-correlated single photon counting spectrometer with a microsecond xenon flash lamp as the source of excitation. The lifetime data obtained for MnGO and MnRGO composites were fitted to a triple-exponential function as, [45][46][47] IðtÞ…”
Section: Resultsmentioning
confidence: 99%